2020
DOI: 10.34119/bjhrv3n1-048
|View full text |Cite
|
Sign up to set email alerts
|

L-PRF E I-PRF associado à hidroxiapatita como material de enxertia na reconstrução de osso alveolar em região anterior de maxila: relato de caso

Abstract: A atrofia dos ossos gnáticos pode estar associada à dificuldades no tratamento protético. Após uma exodontia, por exemplo, o osso sofre remodelação, perdendo volume. Assim, é de extrema importância sua preservação quando existe o planejamento da realização de implante dentário. Diferentes materiais e técnicas foram desenvolvidas e são utilizadas na cirurgia oral, como o PRF, um importante biomaterial. Dentre suas características, estão a promoção da angiogênese, controle imunológico, aproveitamento das células… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In fresh dental sockets, Mattos et al (2016) grafted hydroxyapatite with collagen and L-PRF membrane in the region of tooth #24 with buccal bone wall presenting dehiscence and installed a dental implant, promoting satisfactory osseointegration and rehabilitation in the aesthetic area in 18 months. Silva et al (2020) after remotion of the teeth #21, #22 and #23 used i-PRF to bind synthetic hydroxyapatite and covered the sticky bone with L-PRF membrane, generating an excellent postoperative period and after 6 months, satisfactory bone thickness for implants. Huang, Tan and Kuang (2020) investigated the effect of Bio-Oss® granules with or without PRF in 106 patients with anterior unit tooth loss and alveolar defects and observed that, 12 months after implants and simultaneous GBR, in the group with PRF the thickness of the buccal bone wall and around of implants was higher, the rates of gingival bleeding, probing depth and attachment loss were lower, and the height of bone graft and osteogenesis were greater than xenograft alone.…”
Section: Discussionmentioning
confidence: 99%
“…In fresh dental sockets, Mattos et al (2016) grafted hydroxyapatite with collagen and L-PRF membrane in the region of tooth #24 with buccal bone wall presenting dehiscence and installed a dental implant, promoting satisfactory osseointegration and rehabilitation in the aesthetic area in 18 months. Silva et al (2020) after remotion of the teeth #21, #22 and #23 used i-PRF to bind synthetic hydroxyapatite and covered the sticky bone with L-PRF membrane, generating an excellent postoperative period and after 6 months, satisfactory bone thickness for implants. Huang, Tan and Kuang (2020) investigated the effect of Bio-Oss® granules with or without PRF in 106 patients with anterior unit tooth loss and alveolar defects and observed that, 12 months after implants and simultaneous GBR, in the group with PRF the thickness of the buccal bone wall and around of implants was higher, the rates of gingival bleeding, probing depth and attachment loss were lower, and the height of bone graft and osteogenesis were greater than xenograft alone.…”
Section: Discussionmentioning
confidence: 99%